COMPLEX TREATMENT IN A PATIENT WITH SEVERE CHRONIC PERIODONTITIS (Case Report). - Kamen Kotsilkov; Radoi Dimitrov (Peytchinski Publishing, 2015)
INTRODUCTION: Periodontitis is characterized by progressive destruction of periodontium, caused by relatively small group of microorganisms. The treatment aims to create proper environment which hampers the colonization of pathogens. The mechanical cleaning of the root surfaces combined with meticulous oral hygiene is the consensus treatment. In advanced cases the progression of the disease could lead to different problems - gingival recessions, insufficiency of attached gingiva, mobility and tooth loss which require complex treatment. OBJECTIVE: This presentation demonstrates the multidisciplinary treatment approach in a patient with a severe chronic periodontitis. METHODS: S.S. (42) with severe chronic periodontitis, insufficient mandibular vestibule depth, lack of keratinized gingiva, class III recessions and central incisors with grade III mobility. The #12 is missing and a crossbite is present on #32. The anti-infective therapy led to stable periodontal status. The corrective phase included the creation of vestibule depth with an autogenous gingival graft, dental implant placement with immediate provisional loading for #12, extraction of #31 and #41 due to attachment loss to the apex and immediate placement of provisionals with crossbite correction. RESULT: The reevaluation demonstrated good control of the gingival inflammation and stable periodontal status. The subsequent implant and prosthetic treatment led to the restoration of a functional dentition. CONCLUSION: The long term success of the treatment of the complex cases with severe chronic periodontitis depends significantly upon the proper control of the periodontal infection and the achievement of a stable periodontal status. These are the major prerequisites for successful further implant and prosthetic rehabilitation.